Compensation Fairness and Driver Switching Intention: Evidence from KSU Sedana Murti - I Wayan Julyan Satria Megano; I Gede Mudana; Ni Gst Nym Suci Murni; I Ketut Sutama; Gede Ginaya (Badan Riset dan Inovasi Daerah Provinsi Bali, 2025)
Purpose: This study aims to examine the relationship between compensation fairness and driver switching intention, with empirical evidence drawn from Koperasi Serba Usaha (KSU) Sedana Murti in Bali. Research methods: A mixed-method exploratory sequential design was employed, beginning with qualitative exploration through Focus Group Discussions (FGDs) and in-depth interviews, followed by quantitative analysis using multiple regression. Findings: The qualitative phase revealed that drivers’ reluctance to remain on online platforms is shaped by perceptions of external fairness (full income without commission deductions and competitive fares), internal fairness (transparent operations and proportional incentives), and individual fairness (income adequacy to support personal and family needs). Additional non-financial factors such as professional pride, guest satisfaction, and work comfort also reinforced the preference for tourist taxi systems. Quantitative results confirmed that external fairness (X₁), internal fairness (X₂), and individual fairness (X₃) all significantly affect switching intention (Y), with an Adjusted R² value of 0.907. Among them, individual fairness emerged as the most dominant factor. Implication: These results validate the relevance of Compensation Fairness Theory and Switching Intention Theory within the framework of the Theory of Planned Behavior, demonstrating that perceived fairness strongly drives occupational decisions in Bali’s tourism transport sector.